Efficiency of Supply Chain Management Performance in Potato Farming with Data Envelopment Analysis - Putri, Dindy Darmawati; Fadlillah, Nurfahmi; Suyono, Suyono; Wijayanti, Irene Kartika (Jurnal Penelitian Pendidikan IPA, 2024)
The potato farmers in Karangreja District use two supply chain channels, namely the supply chain channel partnership non-partnership supply chain channels. The existence of a good supply chain channel, will provide benefits and benefits that are evenly distributed to all parties involved in distributing potato products to consumers. The purpose of this research is to analyze the differences in profit, farmer share, and supply chain efficiency in partnership and non-partnership patterns in Karangreja District, Purbalingga Regency. The farmer sampling method using Simple Random Sampling obtained 500 partnership pattern farmers and non-partnership pattern farmers. Determination of marketing agencies using the Snowball Sampling technique obtained collectors, wholesaler, and retailers. Analysis of the data used is the analysis of supply chain efficiency and analysis of different tests. The results of the analysis show the supply chain efficiency analysis shows that 42.86 farmers operating efficiently have partnership patterns and 57.20 non-partner pattern farmers. The different test analysis shows that for profit and farmer's share indicators there is a significant difference between the partnership pattern and the non-partnership pattern. As for the marketing margin indicators and performance efficiency, there is no significant difference between the partnership pattern and the non-partnership pattern